(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Thereis an international consensus that all human rights, civil and political rightson the one side and economic, social, and cultural rights on the other, are ofequal status and interdependent. TheVienna Declaration and Programme of Action of the 1993 World Conference onHuman Rights spells out, ‘All human rights are universal, indivisible andinterdependent and interrelated’. It recognizes that it is not possible torealize any one right without promoting and protecting other rights also. It furthers specifies that the internationalcommunity must treat human rights globally in a fair and equal manner, on thesame footing, and with the same emphasis. . Two most enthusiastic InternationalCovenant on Civil and Political Rights and on Economic, Social and CulturalRights. For making legally bound by therequirements of these Covenants and other international human rightsmechanisms, countries are to ratify the mandates of the documents. Keywords– The Magna Carta, Declaration, Intellectual, Vehemently, Bill of Rights of theUS Constitution, Scientific, Right, Mankind, United Nation Organization.